Analysis of Student Satisfaction with Science Advisory Services During the COVID-19 Pandemic - Sitorus, Parlindungan; Pardede, Hebron; Hutauruk, Agusmanto J.B; Lafau, Bernalenta (Postgraduate, University of Mataram, 2023)
This study aims to determine the level of student satisfaction with the services of FKIP HKBP Nommensen University thesis advisors during the Covid pandemic period 2020-2022. To obtain data on the level of student satisfaction with lecturer guidance services, an instrument was designed in the form of a student satisfaction questionnaire with lecturer guidance services using satisfaction indicators that had been assessed for validity and reliability prior to use. This type of research is descriptive quantitative, the results of the study were analyzed using the SKM method based on a student satisfaction survey. The data analysis carried out showed that the level of student satisfaction during the Covid pandemic was included in the very good and good categories. The results also show that forecasting student perceptions of lecturer guidance services with the assumption that perceptions increase, a satisfaction value of 3.5629 will be obtained in the